Role of species diversity and secondary compound complementarity on diet selection of Mediterranean shrubs by goats. - Rogosic, Jozo; Estell, Richard E.; Skobic, Dragan; Martinovic, Anita; Maric, Stanislava (Journal of chemical ecology, 2006)
Goats foraging on Mediterranean shrubs containing secondary compounds (toxins) may consume a variety of shrubs that contain different phytotoxins, thereby increasing shrub intake and avoiding toxicosis. We conducted eight experiments to examine whether goats offered different mixtures of shrubs containing different phytotoxins (tannins and saponins) would consume more shrub biomass than goats offered one shrub a single phytotoxin (tannin or saponin). In the first three experiments, goats fed a mixture of three tannin-rich shrubs (Quercus ilex, Arbutus unedo, and Pistacia lentiscus) ate more foliage than goats offered only one shrub (23.2 vs. 10.7 g/kg BW; 25.2 vs. 13.4 g/kg BW, and 27.9 vs. 7.9 g/kg BW), regardless of tannin concentration in individual shrub species. Goats also consumed more foliage when offered the same three tannin-rich shrubs than when offered the saponin-rich shrub Hedera helix (25.4 vs. 8.0 g/kg BW). However, goats offered a mixture of the same three tannin-rich shrubs consumed less foliage than goats offered a mixture of two shrubs containing tannins and saponins: Quercus and Hedera (21.6 vs. 27.1 g/kg BW), Arbutus and Hedera (21.8 vs. 27.1 g/kg BW), and Pistacia and Hedera (19.7 vs. 22.0 g/kg BW). Comparison of intake of shrubs containing only tannins or saponins to intake of shrubs containing both tannins and saponins indicated that goats consumed more total biomass when fed with shrubs with both classes of compounds than with either tannins or saponins alone. Our results suggest that goats can increase intake of Mediterranean shrubs high in secondary compounds by selecting those with different classes of phytotoxins. Simultaneous ingestion of shrubs containing tannins and saponins may promote chemical interactions that inhibit toxic effects of these phytotoxins in the intestinal tract. In addition to complementary interactions between tannins and saponins, biological diversity within Mediterranean maquis vegetation also plays a positive role in increasing shrub intake by goats.
The following values have no corresponding Zotero field: accession-num: 16770718
Keywords: Biodiversity; Goats; Maquis; Mediterranean shrubs; Saponins; Secondary compounds; Tannins

The voluntary intake and rumen digestion by grazing goats and sheep of a low-quality pasture from a semi-arid land - Alcaide, E. M.; Garcıa, M. A.; Aguilera, J. F. (Livestock Production Science, 1997)
An experiment was carried out in late autumn with goats and wethers fitted with permanent ruminal cannulae, grazing in a semi-arid area of South Spain. Shrubs were the most available plant species, although natural vegetation also included trees and grasses. In general, the dominant species of the available vegetation accounted for the highest proportion in the selected diet. Similar proportion and species of grasses were found in the pasture selected by goats and wethers, whereas interspecies differences were observed regarding the selection of shrubs and tree species. Crude protein content was similar in selected diets by goats and sheep, but a higher unavailable N proportion was found for sheep (27.1 and 30.0% of total N for goats and sheep, respectively). Digestibility of forage selected was higher for goats than for wethers. Voluntary intake was significantly (P < 0.05) higher in goats than in sheep; the metabolizable energy intake for goats was higher than their maintenance requirements but failed to meet maintenance needs for wethers. Fermentative rumen activity was moderate and similar for goats and sheep. No interspecies differences were found in rumen fermentation parameters except for molar proportions of acetic and propionic acid and for acetic/propionic ratio, which were significantly higher in wethers. The degradation rate tended to be faster in goats, whereas potential and effective degradability tended to be similar in goats and sheep.
Keywords: Goats; intake; rumen fermentation; semi-arid land; Sheep